M. tuberculosis microvariation is common and is associated with transmission: Analysis of three years prospective universal sequencing in England. Issue 1 (July 2022) - Wyllie, David; Do, Trien; Myers, Richard; Nikolayevskyy, Vlad; Crook, Derrick; Peto, Tim; Alexander, Eliza; Robinson, Esther; Walker, A. Sarah; Campbell, Colin; Smith, E. Grace
Highlights: We studied M. tuberculosis isolates from routine TB sequencing in England. We developed an algorithm exploiting the universal sequencing data available. We identified M. tuberculosis mixtures differing by five or fewer nucleotides. Such microvariation was present in at least 5% of infections. Microvariation is associated with isolation patterns compatible with transmission. Abstract: Background: The prevalence, association with disease status, and public health impact of infection with mixtures of M. tuberculosis strains is unclear, in part due to limitations of existing methods for detecting mixed infections. Methods: We developed an algorithm to identify mixtures of M. tuberculosis strains using next generation sequencing data, assessing performance using simulated sequences. We identified mixed M. tuberculosis strains when there was at least one mixed nucleotide position, and where both the mixture's components were present in similar isolates from other individuals, compatible with transmission of the component strains. We determined risk factors for mixed infection among isolations of M. tuberculosis in England using logistic regression. We used survival analyses to assess the association between mixed infection and putative transmission. Findings: 6, 560 isolations of TB were successfully sequenced in England 2016–2018. Of 3, 691 (56%) specimens for which similar sequences had been isolated from at least two other individuals, 341 (9.2%) were mixed. Mixed infection was more common in lineages other than Lineage 4. Among the 1, 823 individuals with pulmonary infection with Lineage 4 M. tuberculosis, mixed infection was associated with significantly increased risk of subsequent isolation of closely related organisms from a different individual (HR 1.43, 95% CI 1.05, 1.94), indicative of transmission. Interpretation: Mixtures of transmissible strains occur in at least 5% of tuberculosis infections in England; when present in pulmonary disease, such mixtures are associated with an increased risk of tuberculosis transmission. Funding: Public Health England; NIHR Health Protection Research Units; European Union.